The Review of pharmacological treatment registered for obesity in Poland - Wyrwał, Julia; Nowak, Karolina; Olejarz, Zuzanna; Drygała, Zuzanna; Zielińska, Zuzanna; Słowik, Magdalena; Nowak, Karolina; Nieć, Maria; Gierlach, Katarzyna; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction: Obesity is a persistent chronic condition. It is associated with an increased risk of premature death and the development of accompanying diseases. According to statistical data, half of the population struggles with excessive body weight, with one in five Poles being obese. [2] Aim: Our study aimed to evaluate the current literature on pharmacotherapy for obesity available in Poland using the PubMed database. We emphasize the crucial importance of an individualized patient approach to attain therapeutic success, aligning with the latest guidelines and scientific research. A brief description of the state of knowledge: In Poland, we have three registered medications intended for the treatment of obesity: naltrexone/bupropion, liraglutide, and orlistat. It’s crucial that they assist in weight reduction, hence they should be used alongside a proper diet and physical activity, not as the sole form of treatment. Using them assists in achieving therapeutic targets determined in partnership with the patient, and lowers levels of particular indicators linked to chronic inflammation and arterial issues. Moreover, they diminish the chances of complications and early mortality due to the advancement of the condition. Summary: Obesity is a serious condition, and there should be no fear in incorporating pharmacotherapy in patients with it. It is incredibly important to effectively treat this disease and take proactive health measures, even at the stage of overweight, considering it as a precursor to obesity.